Chinese Martial Arts in the Republican Era (Revista de Artes Marciales Asiáticas, 2012)
During the beginning of the XXth century, China suffered attacks from foreign powers causing the lost of parts of its territory as well as a challenge to its national pride. The traditional Chinese martial arts were unable to defeat the tactics and modern weaponry that China’s enemies had in their arsenal. Despite the overwhelming odds, the Chinese forces made use of their ingenuity and adapted the ancient weapons and fighting skills succeeding to some extent in slowing down the enemy’s advance. This period witnessed the last time cold weapons would play an important role in modern Chinese warfare.